It's the Little Things (in Viral RNA) - Potužník, Jiří František; Cahová, Hana (mBio, 2020)
Chemical modifications of viral RNA are an integral part of the viral life cycle and are present in most classes of viruses. To date, more than 170 RNA modifications have been discovered in all types of cellular RNA. Only a few, however, have been found in viral RNA, and the function of most of these has yet to be elucidated. Those few we have discovered and whose functions we understand have a varied effect on each virus. They facilitate RNA export from the nucleus, aid in viral protein synthesis, recruit host enzymes, and even interact with the host immune machinery. The most common methods for their study are mass spectrometry and antibody assays linked to next-generation sequencing. However, given that the actual amount of modified RNA can be very small, it is important to pair meticulous scientific methodology with the appropriate detection methods and to interpret the results with a grain of salt. Once discovered, RNA modifications enhance our understanding of viruses and present a potential target in combating them. This review provides a summary of the currently known chemical modifications of viral RNA, the effects they have on viral machinery, and the methods used to detect them.
Keywords: replikace viru; posttranskripční úpravy RNA; messenger RNA; buněčné jádro; Cell Nucleus; retroviruses; RNA, Messenger; Humans; RNA, Viral; RNA modification detection; RNA virus; Virus Replication; RNA modification; RNA virová; lidé; RNA Processing, Post-Transcriptional; viral RNA